Implementation of Independent Learning in Language Skills Effectively - Jumrah Jamil; Sindi Abubakar; Ridalfa Rijal; Riri Lajoni; Jaena Muksin; Nurbaya Naser; Mirnawati Mustafa; Novita S. Soamole; Luki Dahlan; Jufran Nurdin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Not infrequently, we see the rules of class hours that must be fulfilled, making teachers and students unable to focus on learning. Meanwhile, welfare has not yet met the high demands required by policy makers, for example having to complete all learning tools, creating scientific work, the obligation to carry out the tri-dharma of higher education for lecturers by requiring them to publish articles in the Scopus journal. The educational component is a unit that must contribute to each other and must encourage or help each other, because after all the task of education is part of the application of social functions. Based on these phenomena and general descriptions, the authors are interested in making articles about Merdeka Belajar; Between Rhetoric and Application